2021
DOI: 10.1088/1757-899x/1011/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Bio-modified soybean meal as a new protein source for food

Abstract: Soybean meal has long been considered as a plant protein source particularly for animal feedstuff. Nowadays, there is a promising prospect of this material for food processing. However, its protein utilization has drawbacks, such as poor protein solubility and anti-nutritional factors called phytic acid. The phytic acid could be reduced by the addition of phytase, whereas nutrient content enhanced by microbial fermentation. In this study, we analyzed the bio-modified of soybean meal (SBM) through fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the study reported by Chen et al, a solid-state fermentation with Aspergillus oryzae (ATCC 9362) resulted in a 39% reduction of phytic acid ( 15 ). In another study, SBM fermentation with Lactobacillus plantarum decreased phytic acid by 34.13% ( 30 ). As a major anti-nutritional factor in plant sourced feed, phytic acid reduction after probiotic fermentation in many of the feed components including canola meal have been reported ( 23 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study reported by Chen et al, a solid-state fermentation with Aspergillus oryzae (ATCC 9362) resulted in a 39% reduction of phytic acid ( 15 ). In another study, SBM fermentation with Lactobacillus plantarum decreased phytic acid by 34.13% ( 30 ). As a major anti-nutritional factor in plant sourced feed, phytic acid reduction after probiotic fermentation in many of the feed components including canola meal have been reported ( 23 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soybean meal (SBM), contains 40%-50% crude protein and is one of the most important sources of supplemental plant-based protein in the livestock and poultry industry (1,2). However, anti-nutritional factors (ANFs) such as allergenic proteins, glycinin (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and β-conglycinin (52-76 kDa) found within SBM can damage the intestinal structure of young pigs and chickens, leading to poor nutrient absorption and increased incidence of Qi et al 10.3389/fnut. 2023.1123422 Frontiers in Nutrition 02 frontiersin.org diarrhea, which in turn results in poor growth performance (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…16 The amino group (-NH 2 ) in protein molecule can react with formaldehyde, thus improving the thermal stability and water resistance of the resin. 17 Nowadays, soybean meal is mainly used as a raw material for livestock and poultry feed, 18,19 it can also be adopted to make pastry food, 20 health food, 21,22 cosmetics, 23 and antimicrobial materials. 24 Soybean meal can also be applied to prepare soybean protein-based adhesives.…”
mentioning
confidence: 99%